Effects of linker sequence modifications on the structure, stability, and biological activity of a cyclic α‐conotoxin. Issue 6 (November 2016) - Carstens, Bodil B.; Swedberg, Joakim; Berecki, Géza; Adams, David J.; Craik, David J.; Clark, Richard J.
Abstract: The cyclic conotoxin analogue cVc1.1 is a promising lead molecule for the development of new treatments for neuropathic and chronic pain. The design of this peptide includes a linker sequence that joins the N and C termini together, improving peptide stability while maintaining the structure and activity of the original linear Vc1.1. The effect of linker length on the structure, activity and stability of cyclised conotoxins has been studied previously but the effect of altering the composition of the linker sequence has not been investigated. In this study, we designed three analogues of cVc1.1 with linker sequences that varied in charge, hydrophobicity and hydrogen bonding capacity and examined the effect on structure, stability, membrane permeability and biological activity. The three designed peptides were successfully synthesized using solid phase peptide synthesis approaches and had similar structures and stability compared with cVc1.1. Despite modifications in charge, hydrophobicity and hydrogen bonding potential, which are all factors that can affect membrane permeability, no changes in the ability of the peptides to pass through membranes in either PAMPA or Caco‐2 cell assay were observed. Surprisingly, modification of the linker sequence was deleterious to biological activity. These results suggest the linker sequence might be a useful part of the molecule for optimization of bioactivity and not just the physiochemical properties of cVc1.1. © 2016 Wiley Periodicals, Inc. Biopolymers (Pept Sci) 106: 864–875, 2016.